1998
DOI: 10.1002/(sici)1097-4628(19981212)70:11<2241::aid-app18>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

The agglomeration of high molecular mass polyacrylamide in aqueous solutions

Abstract: Size distribution information was used to monitor time-dependent agglomeration in aqueous solutions of a high molecular mass polyacrylamide. Although the individual polymer molecules had diameters in the order of 0.4 m, a high number of agglomerates were seen that may contain four to six polymer chains. As the solution age increased, a significant level of larger microgels (2-15 m) were also detected. The addition of salts or organic cosolvents modified the solvation properties, altering the extent and rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…From Figure 6, R g increased at higher pH* values. In a more acidic medium, HPAM had protonated acrylate anions; this consequently reduced the number of intramolecular bonds36 and reduced R g 43. The values of R g of 20–25 μm at pH* 3.0–3.5 and 120–170 μm at pH* 6.5–7.0 (Figure 6) suggested that there was a high agglomeration of polymer molecules; this was consistent with those reported by Hecker et al,43 who evaluated, by light scattering, the distribution of the R g of HPAM in deionized water with the addition of salts and organic cosolvents with mean values of 0.4 μm to individual polymer molecules.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…From Figure 6, R g increased at higher pH* values. In a more acidic medium, HPAM had protonated acrylate anions; this consequently reduced the number of intramolecular bonds36 and reduced R g 43. The values of R g of 20–25 μm at pH* 3.0–3.5 and 120–170 μm at pH* 6.5–7.0 (Figure 6) suggested that there was a high agglomeration of polymer molecules; this was consistent with those reported by Hecker et al,43 who evaluated, by light scattering, the distribution of the R g of HPAM in deionized water with the addition of salts and organic cosolvents with mean values of 0.4 μm to individual polymer molecules.…”
Section: Resultssupporting
confidence: 86%
“…After IP, the acrylate anion {[CH(COO) − CH 2 ]} behaved as a branched polymer,45 and R g varied nonlinearly as a function of pH*. This behavior suggested that the anion interacted with acrylamide and protonated water,43 as reported for other polymer systems 46. In this pH* range, cation–anion bonds stabilized the bulb [ K 2 > K 1 (Table II)]; this reduced the rate of increase of R g with increasing pH*.…”
Section: Resultsmentioning
confidence: 67%
“…The conformations of the phPAA-FITC molecules were dynamically tracked under epi-fluorescence illumination at De = 41.46 (1 ml/h) and 414.6 (10 ml/h). Here, the observed phPAA-FITC molecules were polymer aggregates; this occurs naturally even at dilute concentrations 21 22 . Details of the molecular imaging setup have been included in the Methods section.…”
Section: Resultsmentioning
confidence: 75%
“…32 × 22 μm (β/α = 1.5), which was obtained by measuring ≈1000 polymer molecules under static conditions. It should be noted that the size of a single PAA molecule 29 (5 × 10 6 g/mol) is ≈1–2 μm, and the larger molecular size observed is the result of molecular aggregation 21 22 . Supplementary Table S2 shows the size distribution of the molecules, which has been subcategorized into 100 μm 2 incremental size ranges.…”
Section: Methodsmentioning
confidence: 98%
“…y a un poids moléculaire ou une longueur de chaîne optimale pour l'efficacité de la floculation [15]. Ce graphique met en évidence une augmentation de Sa turbidité de la surverse en fonction de l'augmentation de la concentration du polymère.…”
Section: Stabilité Des Suspensions Colloïdalesunclassified